2020
DOI: 10.3389/frobt.2020.557606
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Type of Adverse Events During the Use of Stationary Gait Robots—A Systematic Literature Review

Abstract: Robot-assisted gait training (RAGT) devices are used in rehabilitation to improve patients' walking function. While there are some reports on the adverse events (AEs) and associated risks in overground exoskeletons, the risks of stationary gait trainers cannot be accurately assessed. We therefore aimed to collect information on AEs occurring during the use of stationary gait robots and identify associated risks, as well as gaps and needs, for safe use of these devices. We searched both bibliographic and full-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 80 publications
3
48
0
2
Order By: Relevance
“…As this principle of applying forces through contact points is the same for all rehabilitation robots, the following sections refer to not only stationary gait trainers, but rehabilitation robotics in general. Although the hazards identified through our recent review (Bessler et al, 2020) are based on incidents with stationary lower limb robots, comparable hazards have been reported in upper limb and mobile devices (Rocon et al, 2008;He et al, 2017;Schwartz et al, 2018;van Herpen et al, 2019). Although the interface mechanics between human and robot are often comparable, there are some obvious differences, such as lower weight bearing in upper limb rehabilitation robots and different location and surface area of device-skin interface.…”
Section: Identified Hazardssupporting
confidence: 55%
See 4 more Smart Citations
“…As this principle of applying forces through contact points is the same for all rehabilitation robots, the following sections refer to not only stationary gait trainers, but rehabilitation robotics in general. Although the hazards identified through our recent review (Bessler et al, 2020) are based on incidents with stationary lower limb robots, comparable hazards have been reported in upper limb and mobile devices (Rocon et al, 2008;He et al, 2017;Schwartz et al, 2018;van Herpen et al, 2019). Although the interface mechanics between human and robot are often comparable, there are some obvious differences, such as lower weight bearing in upper limb rehabilitation robots and different location and surface area of device-skin interface.…”
Section: Identified Hazardssupporting
confidence: 55%
“…Due to the increased number and surface area of contact points in exoskeleton-type devices opposed to end-effector-type devices, one might expect that the risk of sustaining such an injury is higher when using exoskeleton-type devices. However, the abovementioned systematic literature review (Bessler et al, 2020) showed that was not the case in stationary gait trainers (see also Figure 1). Many events of discomfort or injuries to soft tissue which were reported in end-effector-type device studies were attributed to the safety harness worn by the patient and the amount of body-weight support seemed to have an influence on the risk of soft tissue-related adverse events caused by the harness in exoskeleton-type devices but not in end-effector-type devices.…”
Section: Shear Forces and Frictionmentioning
confidence: 99%
See 3 more Smart Citations